Transforming our world : an analysis on the rhetorical appeals and framing used in the 2030 Agenda for Sustainable Development to persuade people to take action - Hämynen, Hanna (My University, 2025)
This thesis analyses the United Nations’ 2030 Agenda for Sustainable Development and the rhetorical appeals and framing used in it to persuade people to take action. The aim is to answer the following research questions: 1. Are all three rhetorical appeals used in the Agenda? If yes, how are they used? 2. How does the use of appeals frame the issue? 3. How does the use of appeals and the frame created by it attempt to persuade the reader? The theoretical background of the study is based on rhetorical analysis and ethos, pathos and logos (Virtanen and Halmari 2005) and frame analysis (Goffman [1974] 1986 and Entman 1993). The results show that for example words, phrases, metaphors and associations are powerful tools to appeal to the reader and affect thoughts and actions. All in all, language can be used in many ways to persuade the reader which is why I believe it makes for an interesting and important field of study.
Keywords: persuasion, rhetoric, rhetorical analysis, ethos, pathos, logos, framing, frame analysis, sustainability, sustainable development, united nations, un